Analysis of Factors That Influence The Purchase Intention of Electric Vehicles In Indonesia: An Extended Theory of Planned Behavior Approach - Meliana, Meliana; Pangaribuan, Christian Haposan (Journal Of Social Science (JoSS), 2024)
Environmental problems such as climate change, pollution, rising earth temperatures and degradation of the quality of life are crucial today. Electric vehicles are present as an alternative to reducing carbon emissions from conventional vehicles which have a large impact on producing pollutants. This research aims to analyze the influence of environmental concerns, incentives, price value, attitudes, subjective norms and perceived behavioral control on purchase intentions of electric vehicles in the Jabodetabek area using the Theory of Planned Behavior approach. This research is a quantitative research with a total sample of 123 respondents. Data collection was carried out by distributing questionnaires online and the scale used was a Likert scale. The data analysis technique used is Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The tests carried out include testing the inner model and outer model. The test results show that environmental concern has no significant effect on attitude and purchase intention, incentives have a significant effect on attitude but not significant effect on purchase intention, price value has a significant effect on attitude but not significant effect on purchase intention, attitude and perceived behavioral control have a significant effect but subjective norms does not have a significant effect on purchase intention. Attitude succeeded in significantly mediating the influence of incentives and price value on purchase intention. Attitude does not significantly mediate the influence of environmental concern on purchase intention.